ChemInform Abstract: Direct Access to Functionalized 4‐Nitromethyl‐chromenes via a Domino Reaction under Catalyst‐Free Conditions. Issue 47 (November 2015) - Xu, Wengang; Li, Qingcui; Wang, Wangwang; Zheng, Hua; Zhang, Fanglin; Hu, Yunxing
Abstract: The catalyst‐free reaction of α, β‐unsaturated ketones with a nitroalkane (II, IV) yields 4‐nitromethyl‐chromenes of type (III) or (V).